2018
DOI: 10.1001/jamaoncol.2017.5236
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Most Appropriate Primary End Point in Phase 2 Trials of Immune Checkpoint Inhibitors for Advanced Solid Cancers

Abstract: In checkpoint-inhibitor trials, ORR correlated poorly with OS. For future phase 2 studies, 6-month PFS rate is recommended as an end point.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
98
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(106 citation statements)
references
References 56 publications
7
98
0
1
Order By: Relevance
“…Of interest in this study is the finding of encouraging disease control and survival benefit without high objective response rates. As recently reported by others in a large meta analysis of 87 clinical trials of solid tumors treated with immune checkpoint inhibitors, there is a lack of correlation between response rate and survival (31). The reasons for this are uncertain, but it could be due to the triggering of a persistent immune response that maintains durable tumor growth control despite the absence of an immediate elimination of tumor cells.…”
Section: Discussionmentioning
confidence: 97%
“…Of interest in this study is the finding of encouraging disease control and survival benefit without high objective response rates. As recently reported by others in a large meta analysis of 87 clinical trials of solid tumors treated with immune checkpoint inhibitors, there is a lack of correlation between response rate and survival (31). The reasons for this are uncertain, but it could be due to the triggering of a persistent immune response that maintains durable tumor growth control despite the absence of an immediate elimination of tumor cells.…”
Section: Discussionmentioning
confidence: 97%
“…ORR is considered to be an important clinical endpoint for cancer clinical trials . However, several analyses showed that ORR may not be a reliable surrogate for OS . For example, two important anti‐PD1/PD‐L1 phase III combination studies were conducted based on their high ORR in earlier phase trials—epacadostat and pembrolizumab for melanoma, and atezolizumab‐cobimetinib for colon cancer .…”
Section: Anti‐pd1/pd‐l1 Therapy For Hnscc: Future Perspectivesmentioning
confidence: 99%
“…These two studies showed the limitation of ORR as surrogates for OS benefits. Other surrogates for predicting OS benefits have been proposed, including 6‐month PFS rate, milestone survival analyses, or a high ORR (>30%) …”
Section: Anti‐pd1/pd‐l1 Therapy For Hnscc: Future Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations